A Surgical Technique for the Management of Tractional Retinal Detachment in Aggressive Posterior Retinopathy of Prematurity Treated With Intravitreal Bevacizumab. (October 2019) - De la Huerta, Irina; Yonekawa, Yoshihiro; Thomas, Benjamin J.; Capone, Antonio
Abstract : Supplemental Digital Content is Available in the Text.